The Role of The Commission for The Acceleration of Police Reform in Integrating Legal Politics with The Reconstruction of The Constitutional and Legislative Systems - Rengga Kusuma Putra; Lita Tyesta Addy Listya Wardhani; Bagus Hermanto; Willy Naresta Hanum; Aziz Widhi Nugroho (PALAR | PAKUAN LAW REVIEW, 2026)
The institutional reform of the Indonesian National Police (Polri) is a strategic agenda in realizing democratic and just governance. One of the main challenges is the integration of legal politics and the reconstruction of the constitutional system and legislation consistent with national legal principles. This study aims to analyze the role of the Commission for the Acceleration of Indonesian National Police Reform in integrating legal politics with the reconstruction of the constitutional system and legislation, identify supporting and inhibiting factors in the integration process, and evaluate its impact on the effectiveness of Polri institutional reform. The research method used is qualitative with a normative-sociological legal approach, involving legal document analysis, literature studies, semi-structured interviews, and participant observation. The results show that the Commission successfully bridged inter-institutional coordination, regulatory harmonization, and the implementation of institutional practices aligned with the principles of legal politics, thereby increasing the effectiveness of reform. Supporting factors include political support and internal awareness of the Polri, while obstacles arise from overlapping regulations, internal resistance, and limited resources. This study makes a scientific contribution by emphasizing the importance of integration between legal norms and the socio-institutional context for sustainable institutional reform. Keywords: Commission for the Acceleration of Police Reform; Legal Politics; State Reconstruction.